Adult mastocytosis: a review of the Santo António Hospital 's experience and an evaluation of World Health Organization criteria for the diagnosis of systemic disease - Fernandes, I. (2015)
BACKGROUND: Mastocytosis is a clonal disorder characterized by the accumulation of abnormal mast cells in the skin and/or in extracutaneous organs. OBJECTIVES: To present all cases of mastocytosis seen in the Porto Hospital Center and evaluate the performance of World Health Organization diagnostic criteria for systemic disease. METHODS: The cases of twenty-four adult patients with mastocytosis were reviewed. Their clinical and laboratorial characteristics were assessed, and the properties of the criteria used to diagnose systemic mastocytosis were evaluated. RESULTS: The age of disease onset ranged from 2 to 75 years. Twenty-three patients had cutaneous involvement and 75% were referred by dermatologists. Urticaria pigmentosa was the most common manifestation of the disease. One patient with severe systemic mast cell mediator-related symptoms showed the activating V560G KIT mutation. The bone marrow was examined in 79% of patients, and mast cell immunophenotyping was performed in 67% of the participants. Systemic disease was detected in 84% of cases, and 81% of the sample had elevated serum tryptase levels. All the diagnostic criteria for systemic mastocytosis had high specificity and positive predictive value. Bone marrow biopsy had the lowest sensitivity, negative predictive value and efficiency, while the highest such values were observed for mast cell immunophenotyping. Patients were treated with regimens including antihistamines, sodium cromoglycate, alpha-interferon, hydroxyurea and phototherapy. CONCLUSIONS: Cutaneous involvement is often seen in adult mastocytosis patients, with most individuals presenting with indolent systemic disease. Although serum tryptase levels are a good indicator of mast cell burden, bone marrow biopsy should also be performed in patients with normal serum tryptase, with flow cytometry being the most adequate method to diagnose systemic disease.